DEFAULT RISK AND FIRM PERFORMANCE AMONG PROBLEMATIC FIRMS - Sawal, Noor Azira (Journal of Techno-Social, 2013)
This study aims to investigate whether the problematic firms that were listed under PN17 really suffer financial difficulties prior to their fraud perpetration by using the proxy of default risk. Then, the effect of the default risk will be analysed on the performance of problematic firms. As for this study; the results show that the default risk has significant negative effect on firm’s performance among problematic firms. This implies that default risk of problematic firms could negatively affect the firm’s performance. The result of this study could pave way to any agency that monitors the misconducts among listed firms as financial difficulties may give early signal to warn a company of the possibility of severe fraud occurrence in the future. Moreover, the effect of financial difficulties will give some extent of indicators to public on the tendency to commit fraud due to financial desperation. This study could also help in formulating the guidelines on how to mitigate the effect offraud perpetration among firms that faced financial difficulties.